THE USE OF RECIPROCAL STRATEGY IN TEACHING READING COMPREHENSION - Nirma Herlina (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
This study reports on the use of reciprocal strategy in teaching reading comprehension. It aims at investigating the effects of the use of reciprocal teaching strategy on the students’ reading comprehension. The study employed a quasi-experimental design and involved second graders of senior high school in one public school in Riau, Indonesia. 30 students in one class acted as the experimental group, while 30 students in another class acted as the control group. In the study, the researcher acted as the teacher. The study used three types of data collection techniques including reading comprehension tests and a questionnaire. The data was analyzed based on the theories of reciprocal teaching strategy (Palinscar & Brown, 1984; Meyer, 2010, P.41; and Klinger, Vaughn, & Boardman, 2007).The findings showed that there was a significant difference between the experimental and the control groups in terms of the scores. It can be seen from the result of independent t-test of post-test scores, t-value (t= -3.267, df= 59) was higher than critical value (2.00). Moreover, the data from  the questionnaire demonstrated that the reciprocal strategy used in the experimental group provided three effects to the students’ reading comprehension encompassing (1) obtaining clear idea of the concept and of the use of four reading strategies; (2) developing their self-confidence in sharing their ideas; and (3) enjoying learning atmosphere. Based on the findings, it is recommended that English teachers apply this strategy to develop better students’ reading comprehension.